2019
DOI: 10.1016/j.vetmic.2018.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Duck innate immune responses to high and low pathogenicity H5 avian influenza viruses

Abstract: Ducks are the reservoir host of influenza, and are permissive for replication of most strains, yet can elicit robust innate immune responses to highly pathogenic strains. Tissue tropism and viral amino acid differences affect virulence, but we have limited knowledge about how viral differences influence the host innate immune response. Here we compare the innate immune response in Pekin ducks to a recombinant highly-pathogenic avian influenza (HPAI) H5N1 virus and a naturally arising attenuated variant of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 40 publications
6
46
1
Order By: Relevance
“…PKR is upregulated in ducks infected with both HPAI and (to a lesser extent) LPAI virus (Fleming-Canepa et al, 2019) but to date we are unaware of any studies functionally characterizing duck PKR during influenza infection. We previously thought that ducks appeared to be missing the second dsRNA-binding domain (Fleming-Canepa et al, 2019), also confirmed by another group . However, through transcriptomic assembly done in our lab we have since found a transcript of the full-length PKR, which contains the second dsRNA-binding domain previously thought to be missing.…”
Section: Pkrsupporting
confidence: 68%
See 4 more Smart Citations
“…PKR is upregulated in ducks infected with both HPAI and (to a lesser extent) LPAI virus (Fleming-Canepa et al, 2019) but to date we are unaware of any studies functionally characterizing duck PKR during influenza infection. We previously thought that ducks appeared to be missing the second dsRNA-binding domain (Fleming-Canepa et al, 2019), also confirmed by another group . However, through transcriptomic assembly done in our lab we have since found a transcript of the full-length PKR, which contains the second dsRNA-binding domain previously thought to be missing.…”
Section: Pkrsupporting
confidence: 68%
“…RIG-I is upregulated quickly during influenza infection, with a peak at 24 h and expression returning to normal levels in lung, intestine, and spleen when Pekin ducks are infected with both HPAI and LPAI IAV strains (Fleming-Canepa et al, 2019). In these studies, RIG-I is upregulated much more during HPAI infection than LPAI infection.…”
Section: Rig-imentioning
confidence: 73%
See 3 more Smart Citations